Detection Technology for Runway Incursion Prevention in Airport Hot Spot: A Comparative Overview - Li Jiang; Ping Yang; Xiaodan Ma; Hao Yang; Tuo Li; JianHong Yang (Research Highlights in Science and Technology Vol. 7, 2023)
This chapter defines a comparative overview of Detection Technology for Runway Incursion Prevention in Airport Hot Spot. Runway incursions, defined as an occurrence in which a vehicle, aircraft, or person makes an unauthorized transgression onto a runway, have been a focus of aviation safety stakeholders due to their potential for substantial loss of life in the event of a collision. Microwave phased-array radar can provide parameters like the distance, angle, speed, and direction of target detection, according to a study that briefly introduces and analyses several major technical systems used in the detection of active targets in airport hot spots. Compared with the traditional detection technology system, microwave phased-array radar has the advantages of high detection accuracy, low comprehensive cost, and easier acceptance. With the development of technology, phased array radar technology can continuously scan the detection area, accurately detect the distance, angle, speed and other information of the invading target all day long, and actively track and give early warning to the real target.